The impact of input and output market development intervention of the IPMS Project: The case of Meiso Woreda, Oromiya National Regional State, Ethiopia - Abebe, T. (Haramaya University, 2011)
Improving Productivity and Market Success of Ethiopian farmers’ (IPMS) is a project that is being implemented by ILRI at 10 pilot learning woredas in the country to enhance market oriented production so that the country can overcome the problems of poorly developed agricultural production and marketing. Even though the project has been in place for over five years its impact has not been evaluated. Therefore, this study evaluates the impact of input and output market development interventions of the project on institutional and organizational aspect of markets, input use and productivity, total net income, marketed surplus and market orientation of the participant households. For quantitative analysis both program participant and non participant respondents were drawn and cross-sectional survey data were collected from 180 households in Mieso woreda. A propensity score matching method was applied to assess the impact of the project on outcome variables of the treated households. Results show that the market development interventions have a significant and positive impact on the outcome variables measured using different indicators. The intervention has resulted in positive and significant impact on level of input use for onion and goat production of the treated households. Participants earned more total net income on average from commodities of intervention over non-participants and also found to be more market oriented and supplied more of their produce to market over non-participants. However, some outcome variable indicators such as input use for cattle, net income from goat, land allocated for onion and proportion of goat allocated for fattening by participant households are positive but statistically insignificant. The sensitivity analysis also show that results are not sensitive to unobserved selection bias and were robust to the dummy cofounder. These results reveal that market development interventions of such kind play an important role for the overall transformation and development activities of the country.